Hypophysitis: Evaluation and Management. Issue 1 (December 2016) - Faje, Alexander
Abstract Hypophysitis is the acute or chronic inflammation of the pituitary gland. The spectrum of hypophysitis has expanded in recent years with the addition of two histologic subtypes and recognition as a complication of treatment with immune checkpoint inhibitors. Despite the increased number of published cases, the pathogenesis of hypophysitis is poorly understood, and treatment strategies are diverse and controversial. The diagnosis of hypophysitis generally requires histopathologic confirmation. The presentation and clinical course of hypophysitis varies. Hypophysitis can resolve spontaneously, relapse may occur, and some cases can be refractory to treatment.